The Role of Organizational Climate in Mediating the Effect of Transformational Leadership on Job Satisfaction of Taman Prakerti Bhuana Employees - Gusti Komang Trisna Sudiatmika; Ida Bagus Ketut Surya; I Gusti Made Suwandana; Ni Wayan Sri Suprapti (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
Job satisfaction is the positive or negative feeling employees have toward their work, which arises from evaluating various aspects of the job. This study aims to analyze and explain the role of organizational climate in mediating the effect of transformational leadership on the job satisfaction of Taman Prakerti Bhuana employees through an associative quantitative approach using saturated sampling (census) on 86 employees and Partial Least Square (PLS) analysis. The results indicate that transformational leadership has a positive and significant effect on job satisfaction and organizational climate, while organizational climate has a negative and significant effect on job satisfaction and negatively mediates the relationship between transformational leadership and job satisfaction. These findings have theoretical implications for Herzberg’s Two-Factor Theory, in which transformational leadership serves as a motivator factor that can increase job satisfaction, while negative perceptions of organizational climate reflect weaknesses in hygiene factors such as policies, communication, and working conditions, thereby potentially reducing satisfaction even when motivators are fulfilled. The practical implication for the management of Taman Prakerti Bhuana is the need for a comprehensive evaluation of internal policies, communication systems, and work environments to strengthen hygiene factors so that transformational leadership, which is already running effectively, can be supported by a more conducive organizational climate and sustainably enhance job satisfaction.